The Role of Workload in Increasing the Risk of Burnout Syndrome Among Nurses at Aisyiyah Siti Fatimah Tulangan Hospital, Sidoarjo - Eliya Rohmah; Ika Puspita Sari; Fitria Rakhmawati; Dian Natalia; Risna Zubaidah (Journal of Nursing Management Innovations, 2025)
Background of Study: Nurses frequently experience high levels of occupational stress due to demanding workload conditions, leading to Burnout Syndrome (BOS). Burnout is characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment, significantly impacting nurse well-being and healthcare service quality.Aims and Scope of Paper: This study examines the relationship between workload and burnout syndrome among nurses at Aisyiyah Siti Fatimah Tulangan Hospital, Sidoarjo, aiming to identify the prevalence of burnout and its association with workload levels.Methods: This study used a cross-sectional quantitative analytical design, involving 40 nurses from inpatient and outpatient units selected through total sampling. Data were collected using a structured workload questionnaire and the Maslach Burnout Inventory (MBI), which measures three dimensions of burnout: Emotional Exhaustion, Depersonalization, and Decreased Personal Accomplishment. Statistical analysis used the Chi-Square test with SPSS software to determine the significance of the relationship (p < 0.05).Result: The majority of nurses (75%) reported moderate workload, while 25% experienced low workload; there were no cases of high workload. Despite this, the prevalence of burnout was very high, with 82.5% of nurses experiencing moderate burnout and 7.5% experiencing high burnout symptoms. Chi-square analysis confirmed a significant relationship (p < 0.05) between workload and burnout syndrome. Nurses with moderate workload were more likely to experience moderate to high burnout (93.3%). Emotional exhaustion emerged as the most affected component of burnout.Conclusion: This study highlights that even moderate levels of workload can significantly contribute to burnout in nurses. These findings challenge the traditional view that only high workloads cause burnout, suggesting that psychological distress plays a crucial role. These results emphasize the need for effective workload management strategies, mental health support, and institutional interventions